Slang Words Analysis in “Mean Girls” Film - Laksmy Ady Kusumoriny; Malisa Nurauliya Hanifah (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
This study aims at classifying and finding out the meanings of slang words and/or phrases found in Mean Girls film. Every slang word or phrase from the film was classified into their types by using Eric Partridge’s theory (1954). This is a descriptive qualitative method conducted by portraying the possible meanings and the types of slang words or phrases found in the dialogues of the film. Several slang dictionaries and other related references were used to support this study. This study found that there are several types of slang words found in the film. They are: Public-house Slang, Society Slang, Public School and University and The Church..